Integration of refugees into the European education and labour market : requirements for a target group oriented approach - Seukwa, Louis Henri [Herausgeber] (Lang, 2013)
"For the first time in the history of the EU, from 2002 to 2007 asylum seekers and refugees had been explicitly considered in an employment programme trough EQUAL. Despite the success of this programme, EQUAL as a participant-oriented programme was not restarted after 2007. This book analyzes the results achieved by EQUAL with respect to the EU Council Directive laying down minimum standards for the reception of asylum seekers as well as for the promotion of access to education and employment. Based on case studies in four European cities, the question of access to education and training programmes as well as to the labour market for refugees and asylum seekers is examined. The legal, political, structural and individual conditions for the success of such measures are also highlighted." (Verlag, BIBB-Doku)
Keywords: P 1.5 Migranten; I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; G 1.2 Arbeitsmarkt; Asylbewerber; Flüchtling; Bildung; Soziale Integration; Berufliche Integration; Beschäftigung; EQUAL; Italien; Großbritannien; Bundesrepublik Deutschland; Schweden; Hamburg; Europäische Union